A Systematic Literature Review of Hybrid Multi-Criteria Decision-Making and Technique for Order Preference by Similarity to Ideal Solution Methods for Construction Material Supplier Selection - Wibowo, Fransiscus Xavirius Rizky Suryoaji; Pramesti, Nectaria Putri (Civil and Sustainable Urban Engineering, 2026)
Choosing the right supplier is critical in construction supply chain management, as it directly impacts cost, schedule, and material quality. This paper presents a systematic review of the integration of the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) with hybrid Multi-Criteria Decision-Making (MCDM) methods for building material supplier selection. Following the PRISMA procedure and quality assessment criteria adapted from CASP, JBI, and Kitchenham et al., only Scopus-indexed articles from 2020–2025 were considered. Out of 227 initial records, seven studies met all inclusion and quality criteria. Results showed increasing use of hybrid MCDM approaches, primarily in Asian contexts. Common weighting techniques included the Analytic Hierarchy Process (AHP), Best–Worst Method (BWM), and rough set theory, while advanced methods such as Rough–Dombi BWM, game-theoretic approaches, fuzzy–rough systems, and Entropy–G1 weighting were used to handle uncertainty and complex decision problems. Fuzzy-based representations, particularly Triangular Fuzzy Numbers, were widely employed, with evaluation criteria focused on cost, quality, risk, sustainability, and delivery performance. Hybrid MCDM–TOPSIS frameworks generally produced more consistent and structured decision outcomes. However, findings are limited due to the small number of studies. Key research gaps include insufficient empirical validation in developing-country contexts, limited incorporation of sustainability factors, and practical challenges related to data quality and computational complexity. Future research should prioritize real-world applications, integrate sustainability more thoroughly, and develop user-friendly decision-support tools for construction practitioners.